2014
DOI: 10.1371/journal.pone.0115478
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Care Expenditure after the Loss of a Spouse: Data on 6,487 Older Widows and Widowers in the Netherlands

Abstract: BackgroundIn ageing populations, informal care holds great potential to limit rising health care expenditure. The majority of informal care is delivered by spouses. The loss of informal care due to the death of the spouse could therefore increase expenditure levels for formal care.ObjectiveTo investigate the impact of the death of the spouse on health care expenditure by older people through time. Additionally, to examine whether the impact differs between socio-demographic groups, and what health services are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
5
27
1
1
Order By: Relevance
“…This prewidowhood increase cannot be compared with the findings of Mostofsky et al 16 or those of mortality studies10 11 because these lack repeated measures of health outcomes before bereavement. However, our findings for men are somewhat consistent with the results of an earlier Dutch study on healthcare expenditures 42 months before and after widowhood suggesting that the average expenditure level rises a few months before widowhood among individuals over 80 years old, and remains at a heightened level after widowhood 20. Rolden et al 20 suggested that the expenditure levels predominantly rose because of an increased need for formal care after the death of an informal caregiver, rather than an increased need for medical treatment related to the health impact of bereavement.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This prewidowhood increase cannot be compared with the findings of Mostofsky et al 16 or those of mortality studies10 11 because these lack repeated measures of health outcomes before bereavement. However, our findings for men are somewhat consistent with the results of an earlier Dutch study on healthcare expenditures 42 months before and after widowhood suggesting that the average expenditure level rises a few months before widowhood among individuals over 80 years old, and remains at a heightened level after widowhood 20. Rolden et al 20 suggested that the expenditure levels predominantly rose because of an increased need for formal care after the death of an informal caregiver, rather than an increased need for medical treatment related to the health impact of bereavement.…”
Section: Discussionsupporting
confidence: 91%
“…However, our findings for men are somewhat consistent with the results of an earlier Dutch study on healthcare expenditures 42 months before and after widowhood suggesting that the average expenditure level rises a few months before widowhood among individuals over 80 years old, and remains at a heightened level after widowhood 20. Rolden et al 20 suggested that the expenditure levels predominantly rose because of an increased need for formal care after the death of an informal caregiver, rather than an increased need for medical treatment related to the health impact of bereavement. This argument was justified by the fact that the increase in expenditure levels after widowhood was especially high in the long-term care sector.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, married status generally reflects a better financial situation, which has been reported to improve prognosis [36]. Furthermore, unmarried patients may have additional health care expenditures, as spouses are the major source of outpatient/informal care [37]. Previous studies have found that married patients are more likely to receive better quality clinical care, choose better medical centers, be more compliant with medical recommendations, receive more aggressive treatments, and recover better from surgery, all of which contribute to a better prognosis [3840].…”
Section: Discussionmentioning
confidence: 99%